MULTICULTURAL INSIGHT IN PROMOTING TOLERANCE MOVEMENT; LESSON LEARNED FROM ISLAMIC RELIGIOUS EDUCATION IN THE RURAL SIDE - Ahmad Zubaidi (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
Islamic religious education has a very important role in shaping the character and attitude of tolerance of society, especially multicultural and plural societies. In achieving tolerance, patterns of instilling tolerance education between religious communities are needed, the cultivation of tolerance is carried out in the form of an Islamic religious education approach, both in the form of curriculum and community roles. This research aims to analyze the model of Islamic religious education with multicultural insight to increase understanding of tolerance. This research uses a qualitative approach with the type of case study, the research location is in Sukapura District, Probolinggo Regency. data collection techniques using observation, in-depth interviews and documentation, while data analysis uses the theory of Miles, Huberman, and Saldana, namely: data collection, data condensation, presenting data, and drawing conclusions or verification. The results showed that Multicultural Insights in promoting tolerance movement in the rural side, was carried out by four methods; 1) Curriculum integration of Islamic religious education; 2) Internalization through the role of religious and traditional leader; and 3) Internalization through governmental policy and family.